2016
DOI: 10.1080/21645515.2016.1190056
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity of Varicella zoster virus in vaccinated Korean children and MAV vaccine group

Abstract: In 2005, a single-dose varicella vaccination was incorporated into the national immunization program in Korea. Although the Oka strain is the most commonly circulating Varicella zoster virus (VZV) genotype in Korea, a domestically manufactured vaccine based on the MAV strain is widely distributed in Korea. High vaccination coverage was achieved, but breakthrough infections were frequently reported. Therefore, in this study, we aimed to analyze the maintenance of immunity after single-dose vaccination and to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…13 Choi et al also showed a progressive decrease in seropositivity from the age of 1 to 4 years, demonstrating rapidly waning immunity after single-dose varicella vaccination at 12-15 months of age. 31 It seems reasonable to provide the second dose vaccine to children before the substantial waning of vaccine-induced immunity. In our study, all children aged ≤9 years were targeted for the universal varicella vaccination program during 2013-2015.…”
Section: Discussionmentioning
confidence: 99%
“…13 Choi et al also showed a progressive decrease in seropositivity from the age of 1 to 4 years, demonstrating rapidly waning immunity after single-dose varicella vaccination at 12-15 months of age. 31 It seems reasonable to provide the second dose vaccine to children before the substantial waning of vaccine-induced immunity. In our study, all children aged ≤9 years were targeted for the universal varicella vaccination program during 2013-2015.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective cohort study involving students attending elementary school suggested that 99% of one-dose vaccination coverage was not sufficient to prevent varicella outbreaks [22]. A longitudinal seroprevalence study in Korea showed a progressive decrease of the seropositivity rates following vaccination: 65% at age 1 year, 59% at age 2 years, 53% at age 3 years and 49% at age 4 years [23]. One may also postulate that one dose of varicella vaccination may result in secondary vaccine failure, or waning of immunity over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, two clinical trials (2223) and a recent clinical case-control study (11) showed that the vaccine did not ameliorate disease severity and was poorly immunogenic. A recent immunogenicity study on MAV and Oka (Vari-L) vaccine showed that the MAV vaccine generated higher seropositivity rates and antibody titers than the Oka vaccine and provided immunity against VZV, despite waning of immunity observed (24). Not all Oka vaccine in this study, however, were effective against VZV, so it cannot directly be interpreted that MAV vaccine is effective.…”
Section: Discussionmentioning
confidence: 99%